Community Health Nursing Students Identifying Depression in Members of the Community with Diabetes, A Quantitative Approach (International Journal of Nursing Education, 2021)
Background: The aim of this study was to improve depression screening, monitoring, and treatment ofindividuals in community-based programs with co-morbid type 2 diabetes by senior nursing students.Method: This experimental research utilized the Basic Diabetes Knowledge Test (KAT), DepressionKnowledge Questionnaire (MCQ), and the Patient Health Questionnaire -9 (PHQ-9) to measure thedepression and diabetes knowledge of students before and after an educational intervention over timeutilizing ANOVA.Results: The main effect of time for KAT and MCQ is statistically significant (F2=16.74, p
Keywords: community health nursing, type 2 diabetes mellitus, depression, health promotion, comorbidities, referrals